Review of Poverty and the Poor Law in Ireland, 1850-1914, by Virginia Crossman - Josh Newman (Review of Irish Studies in Europe)
Review of Poverty and the Poor Law in Ireland, 1850-1914, by Virginia Crossman (Liverpool: Liverpool University Press, 2019), ISBN-10: 1789620554 ISBN-13:78-1789620559, 272pp. €51.